DEPLOYMENT OF HONEYPOTS AS PROACTIVE DETECTION TOOLS FOR MONITORING CYBER RELATED INCIDENCES - Ogada, Peter Odhiambo; Raburu, George; Liyala, S.; Okelo, N. B (IJRDO -Journal of Computer Science Engineering, 2015)
The Kenya government is striving to roll out its Vision 2030 programme where ICT plays a major role in achieving the components of the Pillars associated with it. The purpose of this study was to find out the extent to which deployment of HoneyPots as early warning detection tools for monitoring cyber related incidents had been embraced within KENET member institutions in Western Kenya, how they are aiding the institutions in knowing and understanding their adversaries; and allowing them to implement solutions that work in defending the critical internet and network infrastructures they manage. The study was guided by a descriptive study design with a study population of 117 staff members working in various institutions in western Kenya. Using simple random sampling technique, a sample size of 80 respondents were picked and administered with questionnaires, 70 questionnaires were returned for data entry and analysis using Statistical Package for social Sciences version 20. This implies that 87.5% of the respondents turned up for the study. According to the major findings, the study established that most of the KENET member institutions in western Kenyan, despite experiencing cyber security related incidents, had not setup CIRT teams nor deployed Honeypots to help them study cyber security incidents and take appropriate action to defend their constituencies. As a recommendation, the Government, being one of the economic stakeholders, and KENET, should come up with intervention measures through the Ministry of ICT making it mandatory for setup CIRTs. All CIRTs should then be required to direct part of their traffic to the national CERT which ideally should be based at Communication Authority of Kenya to form a Honey Net, which can further be linked with other internationally recognized Honey Net projects